"At-home ethnography": Insider, outsider and social relations in rural drinking water management in Chile. Issue 2 (10th May 2018) - Suarez Delucchi, Adriana Angela
Abstract : Purpose: The purpose of this paper is to problematise the idea of "at-home ethnography" and to expand knowledge about insider/outsider distinctions by using insights from institutional ethnography (IE). It also examines the strengths and challenges of "returning" researchers recognising their unique position in overcoming these binaries. Design/methodology/approach: IE is the method the researcher used to explore community-based water management in rural Chile. The researcher is interested in learning from rural drinking water organisations to understand the way in which their knowledge is organised. The data presented derived from field notes of participant observation and the researcher's diary. Findings: The notion of "at-home ethnography" fell short when reflecting on the researcher's positions and experiences in the field. This is especially true when researchers return to their countries to carry out fieldwork. The negotiation of boundaries, codes and feelings requires the researcher to appreciate the complex relationships surrounding ethnographic work, in order to explore how community-based water management is done in the local setting, without forgetting where the setting is embedded. Originality/value: Unique insights are offered into the advantages and tensions of conducting fieldwork "at home" when the researcher has lived "abroad" for an extended time. A critique and contribution to "at-home ethnography" is offered from an IE perspective.